A large-scale database of T-cell receptor beta sequences and binding associations from natural and synthetic exposure to SARS-CoV-2 - Nolan, Sean; Vignali, Marissa; Klinger, Mark; Dines, Jennifer N.; Kaplan, Ian M.; Svejnoha, Emily; Craft, Tracy; Boland, Katie; Pesesky, Mitchell W.; Gittelman, Rachel M.; Snyder, Thomas M.; Gooley, Christopher J.; et al. (Frontiers in Immunology, 2025)
We describe the establishment and current content of the ImmuneCODE™ database, which includes hundreds of millions of T-cell Receptor (TCR) sequences from over 1,400 subjects exposed to or infected with the SARS-CoV-2 virus, as well as over 160,000 high-confidence SARS-CoV-2-associated TCRs. This database is made freely available, and the data contained in it can be used to assist with global efforts to understand the immune response to the SARS-CoV-2 virus and develop new interventions.